2003
DOI: 10.1128/jb.185.16.5003-5006.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Cell Wall Biosynthesis inMycobacterium avium

Abstract: The cell wall of the environmental pathogen Mycobacterium avium is important to its virulence and intrinsic antimicrobial resistance. To identify genes involved in cell wall biosynthesis, "transposome" insertion libraries were screened for mutants with altered colony morphology on medium containing the lipoprotein stain Congo red. Nineteen such mutants were isolated and mapped, including 10 with insertions in a functional island of cell wall biosynthetic genes that spans approximately 40 kb of the M. avium gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Similar to Mu transpososome mutagenesis of Grampositive staphylococci and streptococci (this study), Tn5 transpososomes have been used to directly mutagenize Gram-positive corynebacteria, mycobacteria and rhodococci (Derbyshire et al, 2000;Fernandes et al, 2001;Laurent et al, 2003;Oram et al, 2002;Takayama et al, 2003;Tanaka et al, 2002). In most cases, the reported genomic integration efficiencies were similar to those obtained in our study, and in some cases they were even higher.…”
Section: Discussionsupporting
confidence: 64%
“…Similar to Mu transpososome mutagenesis of Grampositive staphylococci and streptococci (this study), Tn5 transpososomes have been used to directly mutagenize Gram-positive corynebacteria, mycobacteria and rhodococci (Derbyshire et al, 2000;Fernandes et al, 2001;Laurent et al, 2003;Oram et al, 2002;Takayama et al, 2003;Tanaka et al, 2002). In most cases, the reported genomic integration efficiencies were similar to those obtained in our study, and in some cases they were even higher.…”
Section: Discussionsupporting
confidence: 64%
“…It has 5,990 amino acids, about equal in size to the combined PstA (2,552 amino acids) and PstB (3,445 amino acids) proteins of M. avium subspecies hominissuis. In silico analysis of functional modules suggested that PstA plus PstB of M. avium subspecies hominissuis and Mps of M. smegmatis perform similar functions and differ from each other mainly by virtue of their separation into two adjacent genes in some MAC strains (15). The pstAB locus mutagenized in this study is the same one that was mutationally correlated with biofilm formation by M. avium subspecies hominissuis strain A5 (27).…”
Section: Resultsmentioning
confidence: 68%
“…The WO colony type is associated with increased virulence and multidrug resistance relative to opaque colonies that stain red (RO) on Congo red agar (4,19). Mutants with altered colony morphology were isolated and characterized (5,15,21).…”
Section: Resultsmentioning
confidence: 99%
“…The phenotypes of these strains were also investigated on Congo red agar plates. Congo red is a vital dye that binds to lipoproteins or lipids present on the mycobacterial surface (39) and is used to characterize modifications affecting the cell wall (11,22,29 (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%